Sweeney Todd. The Demon Barber of Fleet Street - Logan, John, 1961-; MacDonald, Laurie; Parkes, Walter F.; Zanuck, Richard D.; Burton, Tim, 1958-; Depp, Johnny; Bonham Carter, Helena, 1966-; Rickman, Alan.; Spall, Timothy, 1957-; Baron Cohen, Sacha, 1971-; Wisener, Jayne; Bower, Jamie Campbell; et al. (Hollywood, Calif. : Paramount Home Entertainment, 2008)
Reinventing himself as Sweeney Todd, a man unjustly sent to prison returns to exact revenge on those who ruined his life, especially the evil Judge Turpin who sent the man to prison. Not only does he seek revenge for the cruel punishment he suffered in prison, but also for what happened to his wife and daughter. When he returns to his home town, he reopens his barber shop, where Mr. Todd becomes the Demon of Fleet Street. Mrs. Lovett is Sweeney's amorous accomplice who creates diabolical meat pies out of the remains of Mr. Todd's victims.
DVD ; Region 1 ; widescreen (1.85:1) presentation ; Dolby Digital 5.1 surround.
In English, dubbed French or dubbed Spanish, with English, French or Spanish subtitles.
Closed-captioned.
Johnny Depp, Helena Bonham Carter, Alan Rickman, Timothy Spall, Sacha Baron Cohen, Jayne Wisener, Jamie Campbell Bower, Laura Michelle Kelly, Ed Sanders, Anthony Head, Peter Bowles.
Director of photography, Dariusz Wolski ; editor, Chris Lebenzon ; music and lyrics, Stephen Sondheim ; costume designer, Colleen Atwood ; production designer, Dante Ferretti ; visual effects supervisor, Chas Jarrett.
Based on the musical by Stephen Sondheim and Hugh Wheeler and the musical adaptation by Christopher Bond.
Keywords: Todd, Sweeney (Legendary character) -- Drama; Barbers -- England -- London -- Drama; Serial murderers -- England -- London -- Drama; Revenge -- Drama; Meat grinders -- England -- London -- Drama; Fleet Street (London, England) -- Drama; Barbería -- Inglaterra -- London -- Teatro; Delitos -- Inglaterra -- London -- Teatro; Todd, Sweeney (Legendary character) -- Drama; Barbers -- England -- London -- Drama; Serial killers -- England -- London -- Drama; Revenge -- England -- London -- Drama; Meat grinders -- England -- London -- Drama; Fleet Street (London, England) -- Drama; Feature films; Slasher films; Musical films; Thrillers (Motion pictures, television, etc.); Video recordings for the hearing impaired; Slasher -- Feature; Musical -- Feature; Thriller -- Feature; Feature films; Horror films; Musical films; Suspense films